Fetal and neonatal exposure to AZT and low-protein diet affects glucose homeostasis: a model with implications for AIDS prevention. - Morten, K; Field, P; Ashley, N; Williams, K; Harris, D; Hartley, M; Clark, A; Poulton, J (2005)
Zidovudine (AZT) lowers the perinatal transmission of HIV but can impair mitochondrial function by depleting mitochondrial DNA (mtDNA). AZT therapy and perinatal nutritional deprivation affect the body fat distribution, which influences glucose tolerance. We sought to model intrauterine exposure to AZT in humans to determine whether it interacts with low-protein diet (LPD) to impact on birth weight and glucose homeostasis in the offspring. Pregnant dams and their offspring were given AZT, an LPD, or AZT and an LPD (LPD + AZT). AZT reduced mtDNA copy number in liver and birth weight in the offspring and increased their fasting glucose and insulin (P = 0.021, 0.03, 0.001, and 0.011 respectively) at 6-8 wk of age. LPD decreased litter size and birth weight (P = 0.01 and 0.012). In the LPD + AZT group, birth weight and litter size were reduced compared with untreated controls, and fasting blood glucose and insulin were raised. There was a significant interaction between LPD and AZT on fasting insulin levels (P = 0.025). Islet size was not significantly affected, but the mean beta-cell area/islet was reduced in the LPD + AZT group compared with controls (P < 0.05). Early exposure to AZT interacts with LPD to impair fetal development in this model. This combination appeared to impair the supply of insulin and, hence, glucose homeostasis, perhaps as a result of impaired mitochondrial function. Although it is not certain that this can be extrapolated to humans, maternal nutritional deprivation combined with AIDS therapy could influence both birth weight and onset of diabetes.